Beyond disruption : technology's challenge to governance - Shultz, George P., 1920-2021; Hoagland, Jim; Timbie, James (Hoover Institution Press publication, 2018)
In Beyond Disruption: Technology's Challenge to Governance, experts from academia, media, government, and the military wrestle with understanding the nature of these technologies' threats to our societies and their great potential for our economies. In a series of vivid analyses and colorful commentary from a conference as Stanford University's Hoover Institution, the authors expand upon their first-hand interpretations of what's at stake for the global operating system in the midst of turbulent change. In the dynamic game of world order, it's a primer for decision makers on where the puck is headed.